Study on multidimensional changes of rainfall erosivity during 1970–2017 in the North–South Transition Zone, China - Li, Li; Zhu, Wenbo; Liu, Junjie; Zhang, Li; Zhu, Lianqi; Wang, Liyuan; Chen, Chaonan; Ahmed, Naveed; Gurung, Sher Bahadur (Frontiers in Environmental Science, 2022)
Abstract: Rainfall is a crucial factor causing soil erosion. Therefore, assessing rainfall erosivity (RE) is pivotal to accurately forecast soil erosion. Based on the daily precipitation records from 118 meteorological stations from 1970 to 2017 in Qinlin-Daba mountains (Qinba mountains), the daily rainfall model and statistical methods were applied to investigate the Spatio-temporal changes of RE and identify the evolution law of RE considering the change of latitude, longitude, and topographic relief. The results show: (i) The study area's average annual RE (AARE) was 4,197.85 MJ mm hm-2 h-1 a-1 from 1970 to 2017, displaying a slight variation with a mutation coefficient of 0.16. (ii) The spatial distribution of RE is high in the Southeast and low in the northwest, and the mean annual RE declines with the increase in latitude in longitude and increases with the reduction in longitude in latitude. (iii) Rainfall is the dominant factor affecting RE (q=0.97), while Normalized Difference Vegetation Index (NDVI) has the weakest influence (q=0.24). The influencing factors of RE were ranked as rainfall, temperature, longitude, DEM=topographic, and NDVI.